Toothache referred from auriculotemporal neuralgia: case report - Murayama, R. A. [UNESP]; Stuginski-Barbosa, J.; Moraes, N. P.; Speciali, J. G. (Wiley-Blackwell Publishing, Inc, 2009)
P>AimTo present a 52-year-old male patient who complained of intense pain of short duration in the region of the left external ear and in the ipsilateral maxillary second molar that was relieved by blockade of the auriculotemporal nerve in the infratemporal fossa.SummaryExtra- and intraoral physical examination revealed a trigger point that reproduced the symptoms upon finger pressure in the ipsilateral auriculotemporal nerve and in the outer auricular pavilion. The patient's medical history was unremarkable. The maxillary left second molar tooth was not responsive to pulp sensitivity testing and there was no pain upon percussion or palpation of the buccal sulcus. Periapical radiographs revealed a satisfactory root filling in the maxillary left second molar. on the basis of the clinical signs and symptoms, the auriculotemporal was blocked with 0.5 mL 2% lidocaine and 0.5 mL of a suspension containing dexamethasone acetate (8 mg mL(-1)) and dexamethasone disodium sulfate (2 mg mL(-1)), with full remission of pain 6 months later. The diagnosis was auriculotemporal neuralgia.Key learning pointAuriculotemporal neuralgia should be considered as a possible cause of nonodontogenic toothache and thus included in the differential diagnoses.The blockade of the auriculotemporal nerve in the infratemporal fossa is diagnostic and therapeutic. It can be achieved with a solution of lidocaine and dexamethasone.
Keywords: anaesthesia; auriculotemporal neuralgia; local; toothache